Glove Puppet as a Distraction Method: Reducing Hospitalization Response in Preschool Children During Injections - Faridah Faridah; Diyah Arini; Iis Fatimawatai; Ainin Ulifah (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Hospitalization and medical procedures such as injections are common causes of anxiety and behavioral distress in preschool children. Non-pharmacological, atraumatic care such as distraction technique is an imperative to reverse such reactions. This study aimed to analyse the effectiveness of glove puppets as a distraction method in reducing hospitalization-related behavioural responses in preschool children undergoing injection procedures. Methods: This quasi-experimental pretest–post-test non-equivalent control group study was conducted among 32 preschool children aged 3–6 years hospitalized at Dr. Ramelan Naval Hospital, Surabaya, Indonesia. Participants were assigned to an intervention group (n = 16) and a control group (n = 16). Behavioural responses were assessed using a validated observational checklist before and after the injection procedure. Glove puppet distraction therapy was administered to the intervention group prior to the injection procedure. Data were analysed using the McNemar test to evaluate categorical changes and the Wilcoxon test to compare pre–post scores. Results: Before the intervention, 87.5% of children in the intervention group and 75% in the control group exhibited high levels of behavioural distress. After the intervention, the proportion of high distress in the intervention group decreased significantly to 25%, while no meaningful change occurred in the control group (81.3%). A significant reduction in distress was observed in the intervention group (p < 0.001; Cohen’s d = 1.56). Conclusion: Glove puppet distraction is a simple, cost-effective, and developmentally appropriate strategy that significantly reduces hospitalization-related behavioural distress among preschool children.